Farnesyltransferase inhibitors decrease matrix-vesicle-mediated mineralization in SaOS-2 cells - Tim Bürgel; Daniel Diehl; Elisabeth-Cosima van Lier; Anton Friedmann; Anna Hagemann; Hagen S. Bachmann (Molecular Biology Reports, 2026)
Background Farnesyltransferase inhibitors (FTIs) were developed for preventing the prenylation of aberrant Ras in human cancer. Furthermore, prenylation is involved in multiple biological processes and plays a putative role in signalling pathways such as the Ras-mitogen-activated-protein kinase (MAPK) pathway. Matrix-vesicle-mediated mineralization (MVM) is the first step in the development of eukaryotic mineralized tissue. In this study, we evaluated the effect of FTIs on MVM in the osteosarcoma cell line SaOS-2 and elucidated the role of farnesylation in this process. Methods SaOS-2 cells were treated with the FTIs Lonafarnib and Tipifarnib. Mineralization was assessed using Alizarin Red S staining. Enzyme assays were conducted to measure alkaline phosphatase (ALP) activity. Western blot analysis and Oxford Nanopore sequencing were performed to evaluate the expression of ALP, collagen type I (COL1A1), and Runt-related transcription factor 2 (RUNX2). Results Inhibition of farnesylation by FTIs resulted in decreased mineralization, as evidenced by reduced Alizarin Red S staining. Additionally, RUNX2 activity was diminished, leading to a reduction in MVM and decreased expression of ALP and COL1A1. Conclusion Our findings demonstrate that FTIs Lonafarnib and Tipifarnib impair MVM, highlighting the essential role of farnesylation in biomineralization.